The effect of the chilled water temperature on the performance of an experimental air-cooled chiller - Huong, Phan Thi Thu; Hong, Hoang Mai; Anh, Lai Ngoc (Vietnam Journal of Mechanics, 2021)
This paper presents the study results on the effect of the chilled water temperature on the coefficient of performance (COP) of an experimental air-cooled chiller. The measuring sensors and instrument were calibrated, and the uncertainty of the measuring temperature and pressure were evaluated. The uncertainty of measured temperature and pressure at 95% confidence level is 0.12 °C and 1.4 kPa, respectively. The isentropic compression efficiency and the COP of the air-cooled chiller operating at a condensation temperature of 48.05 °C and evaporation temperature of 3.17 °C are 63% and 2.69, respectively. The chilled water temperature has a significant influence on evaporation pressure and the COP of the chiller. If the temperature of the air entering the condenser of the chiller is maintained at 35 °C, the COP of the chiller increases from 2.55 to 2.89 when the temperature of the chiller water increases only 4 K, from 8 °C to 12 °C.